FUTURIST CONFLUENCES IN ULTRAISM - Alessandro Ghignoli (Filolog, 2025)
Our study focuses on the relationship between the Italian futurist avant-garde and Spanish ultraism. We will see how, above all, the movement founded in 1909 by Filippo Tommaso Marinetti will be present in the literary and cultural journey, albeit brief in comparison to the Italian one, of the Iberian avant-garde, which will be able to read the poetic guidelines that refer to a certain anti-passatism and a syntactic rethinking of writing on the one hand, and to certain formulas of public presentations such as the ‘serate’ (evenings), as well as contacts, fundamentally in the futurism-ultraism direction, in the different magazines that sprang up around the avant-garde at the time. The idea of contacts and closer relations, as we will verify, will be present in the readings of the various authors of the two avant-garde movements.